PROGRAMAS “SEGUNDO TEMPO” E “MAIS EDUCAÇÃO” E SEUS DESDOBRAMENTOS: O ESPORTE NO CONTEXTO ESCOLAR NA PERSPECTIVA DOS PROFESSORES DE EDUCAÇÃO FÍSICA - Grando, Daiane (2015)
This work aims to study the sport in schools and their educational principles from the perspective of Second Time Program that is integrated to More Education Program (PSTPME). The central research question seeks to answer: How is the development of sport in the school and its educational principles in PST-PME in the pedagogical perspective of physical education teachers? The research objectives are: a) to analyze the development of sports in the school and its educational principles in PST-PMEs, in the pedagogical perspective of physical education teachers; b) to identify the theoretical and methodological assumptions of Second Time Program (PST); c) to identify the theoretical and methodological assumptions of the PST-PME; d) to clarify what is the understanding of the physical education teachers about the theoretical and methodological assumptions of the PST-PME; e) to verify what are the methodological theoretical presuppositions underlying the pedagogical actions of physical education teachers in the development of sport in school. The theoretical contribution of the work is subsidized by studies that address the social role of sport (Gramsci 1976; Cury, 1983; SEMERARO, 1999; Coutinho, 2011; Barbieri, 1999; BRACHT, 2000 COLLECTIVE AUTHORS, 1992; GEBARA 2002 ; Lucena, 2001); Sport Pedagogy and its contributions to the development of educational sports (Reverdito; SCAGLIA, 2009; PAES; BALBINO, 2005); Sport and social programs (TUBINO 1996, 2010; BORGES, 2009) and historical aspects, concepts and objectives related to sports social programs (TAFFAREL, 2012; ATHAYDE, 2009; Ferreira, 2012; Santos, Oliveira, 2009). The methodological basis is a descriptive qualitative approach. The survey was conducted in three (3) public schools in the municipality of Guarapuava-PR, where the Programs Second Time integrated to More Education is developed, and had as subjects of study three (3) physical education teachers who work in that program . As instruments for data collection were used to document analysis, observation of classes and interviews with the teachers. For analysis and discussion of the data it was used the Content Analysis (Bardin, 2011). Through the analysis of data It was noticed that the development of sport in the PST-PME occurs in a context permeated by contradictions, both for physical and material resources, and with regard to understanding and application of its pedagogical rationale. The PST-PME constitutes a space in which children at social risk can play, as well as, play and have fun. In this sense, the sport is seen as a means to fill the downtime and mitigate social issues. It was concluded that the sport and its development through programs and social projects related to school contributes to the effective actions designed to meet the needs and interests of the population.